Complex electrolyte additive for battery, aqueous zinc ion battery electrolyte and aqueous zinc ion battery

By using Cu-EDTA complex as an electrolyte additive in aqueous zinc ion batteries, the deposition behavior of zinc ions and slowing side reactions are regulated, and the dendrite, corrosion, hydrogen evolution and passivation problems of zinc negative electrodes are solved, which significantly improves the cycle stability and rate performance of the battery.

CN119852565APending Publication Date: 2025-04-18GUANGXI NORMAL UNIV

Patent Information

Application Number
CN202510154964.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The dendrite, corrosion, hydrogen evolution and passivation problems of zinc negative electrodes in aqueous zinc ion batteries lead to unstable battery performance, affecting cycle magnification and reversibility.

Method used

Complex electrolyte additives, such as Cu-EDTA complexes, are used to form metal or alloy electrode-electrolyte interfaces to regulate the deposition behavior of zinc ions, inhibit dendrite growth, optimize the solvation structure of zinc ions, and slow down side reactions.

Benefits of technology

It significantly improves the cycling stability and rate performance of the zinc negative electrode, extends the life of the zinc negative electrode, enhances the Coulomb efficiency of the battery, and reduces capacity attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852565A_ABST
    Figure CN119852565A_ABST
Patent Text Reader

Abstract

The invention discloses a complex electrolyte additive for a battery, an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. The electrolyte additive is a complex containing metal complex ions; the complex is composed of a central ion and an internal ligand. The electrolyte additive can respectively form metal and alloy electrode-electrolyte interfaces on the surface of a zinc negative electrode through replacement and electrochemical reaction, and regulate and control the deposition behavior of zinc ions to inhibit the generation of zinc dendrites and accelerate deposition / dissolution kinetics, so that the service life of the zinc negative electrode is remarkably prolonged, and the rate capability is enhanced; a solvation structure of zinc ions can be regulated and controlled, side reactions such as hydrogen evolution, corrosion and passivation are slowed down, and capacity fading of the water-based zinc ion battery can be remarkably delayed when the positive electrode is coupled with a high-efficiency positive electrode; meanwhile, the aqueous zinc ion battery electrolyte additive is low in price, green, environment-friendly, high in functionality and beneficial to development of an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery which are excellent in performance, safe, environment-friendly and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc ion batteries, and in particular relates to a complex electrolyte additive for a battery, an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. Background Art

[0002] Nowadays, lithium-ion batteries (LIBs) have been used as the most widely used energy storage system in our daily lives. However, the shortage of lithium resources, environmental pollution, high cost, flammability and explosion have forced us to explore a more low-cost, safe and stable energy storage system.

[0003] In recent years, aqueous zinc-ion batteries (AZIBs) have attracted great attention due to their low cost, environmental friendliness, safety, high energy density (zinc anode: volume density 5851 mAh cm -3 ; Mass density 820mAh·g -1 ) and can work relatively stably in aqueous solution (zinc reduction potential: -0.76 V vs. SHE), making it stand out among many energy storage systems.

[0004] However, the uncontrollable deposition / stripping dynamics of zinc anode in weakly acidic zinc salt electrolyte will lead to the rapid growth of dendrites. On the one hand, dendrites are easy to break to form "dead zinc", which leads to continuous consumption of zinc and eventually failure; on the other hand, dendrites are easy to pierce the diaphragm and cause battery short circuit problems. In addition, due to thermodynamic instability, the deposition process of zinc anode is often accompanied by irreversible hydrogen evolution reaction (HER), which leads to the loss of zinc anode and the increase of local pH, which will accelerate the accumulation of inert products (basic zinc sulfate, zinc hydroxide, zinc oxide, etc.) on the zinc anode, leading to negative electrode passivation and seriously reducing the coulombic efficiency of the battery. These challenges have seriously restricted the development and practical application of aqueous zinc-ion batteries.

[0005] In response to the above challenges, researchers have conducted extensive research on zinc anodes and proposed many effective strategies to improve the deposition / dissolution kinetics of zinc anodes, inhibit zinc dendrites, slow down hydrogen evolution, corrosion and passivation reactions. The current mainstream measures include constructing an artificial interface layer of zinc anodes, structural modification of zinc anodes, diaphragm modification and electrolyte optimization. Among them, the simplest and most efficient strategy for electrolyte optimization is to add electrolyte additives, whose mechanism of action at zinc anodes includes forming an electrostatic shielding layer, inducing uniform deposition of zinc ions, promoting zinc ion desolvation, improving zinc ion flux, etc. However, most of the organic molecular additives currently studied are expensive, have toxic risks (such as dimethyl sulfoxide and organic substances such as benzene, aldehydes, and amides), and have single functions. In addition, if a highly stable zinc anode is to be achieved, the amount of additives required is difficult to estimate.

[0006] Chinese patent application CN113948779A discloses a zinc ion battery electrolyte containing additives, a preparation method thereof, and a zinc ion battery. The zinc ion battery electrolyte disclosed therein contains additives, electrolyte salts, and solvents; the additives therein will produce precipitates as the pH value of the electrolyte increases, and the precipitates will not dissolve with the change of pH. When the electrolyte is applied to the battery, based on the change of environmental pH at the contact interface between the electrode material and the electrolyte, an inorganic solid protective film can be formed on the surface of the electrode material to prevent the material from directly contacting the electrolyte, thereby avoiding the material from being corroded and dissolved by the electrolyte, and improving the cycle stability of the positive and negative electrode materials. Although the above method forms a protective film, which has a certain inhibitory effect on corrosion and dendrite growth, it still cannot avoid the phenomenon of byproducts produced by corrosion during the initial cycle, which has an adverse effect on the flatness of the protective film, and the uneven deposition of metal zinc on the protective film will also cause dendrite growth. In addition, as the battery runs, a thicker and thicker precipitate film will be produced on the electrode surface, resulting in increased battery polarization and affecting the cycle performance.

[0007] Therefore, there is an urgent need for an inexpensive, multifunctional and efficient electrolyte additive to stabilize the zinc anode, which is of great significance for constructing high-performance and high-durability aqueous zinc-ion batteries. Summary of the invention

[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a complex electrolyte additive for a battery, an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. The electrolyte can effectively inhibit the problems of dendrites, corrosion, hydrogen evolution and passivation of the zinc negative electrode, so as to improve the electrochemical performance, cycle rate stability and reversibility of the aqueous zinc ion battery. The process of the present invention is simple and the effect is significant, and it has great potential in promoting the industrial application of aqueous zinc ion batteries.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] A complex electrolyte additive for a battery, the electrolyte additive is a complex containing a metal ligand ion; the complex consists of a central ion and an internal ligand.

[0011] Preferably, the central ion is Cu 2+ , Cu + , Fe 3+ , Fe 2+ 、Co 2+ , Sb 2+ 、Cd 2+ , Gd 3+ , Ga 3+ Sn 2+The internal ligand is one or more of acetylacetone, pyrophosphate, ethylenediaminetetraacetic acid, hydroxyethylethylenediaminetriacetic acid, tartaric acid, citric acid, nitrilotriacetic acid and their salts.

[0012] Preferably, the molar ratio of the central ion to the internal ligand is between 1:10 and 10:1.

[0013] More preferably, the central ion of the complex is Cu 2+ , the internal ligand is EDTA, and the molar ratio of the central ion to the internal ligand is 1:1, that is, the electrolyte additive used is a Cu-EDTA complex.

[0014] The present invention also protects an electrolyte for an aqueous zinc ion battery, wherein the electrolyte contains the complex electrolyte additive for the battery as described above, and the addition amount of the electrolyte additive is 0.001-20 g / L.

[0015] More preferably, the amount of the electrolyte additive added is 1 g / L.

[0016] Preferably, the electrolyte further includes a zinc salt electrolyte and an aqueous solvent, the zinc salt electrolyte is one or more of zinc sulfate, zinc chloride, zinc perchlorate, zinc bromide, zinc acetate, zinc nitrate, zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonyl imide and hydrates thereof, and the concentration of the zinc salt electrolyte is 1-3 mol / L.

[0017] More preferably, the zinc salt electrolyte is zinc sulfate heptahydrate with a concentration of 2 mol / L.

[0018] Preferably, the electrolyte further comprises an additional salt, wherein the additional salt contains Mn 2+ The salt is one or more of manganese sulfate, manganese chloride, manganese perchlorate, manganese bromide, manganese acetate, manganese nitrate, manganese trifluoromethanesulfonate, manganese bis(trifluoromethanesulfonyl imide) and hydrates thereof, and the concentration of the additional salt is 0.01-4 mol / L.

[0019] More preferably, the additional salt is manganese sulfate monohydrate with a concentration of 0.2 mol / L.

[0020] Preferably, the electrolyte can also be used in aqueous zinc ion supercapacitors and aqueous zinc-iron flow batteries.

[0021] The present invention also protects an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte as described above.

[0022] Preferably, the positive electrode comprises a positive electrode active material and a positive electrode current collector, and the positive electrode active material is at least one of a manganese-based material, a vanadium-based material, a Prussian blue analogue, polyaniline, elemental iodine, and basic zinc sulfate, and is preferably δ-MnO2.

[0023] The positive electrode current collector is at least one of titanium foil, titanium mesh, stainless steel foil, stainless steel mesh, carbon paper, carbon cloth, and nickel foam, preferably titanium foil.

[0024] The negative electrode is made of zinc metal material, including any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy, and three-dimensional zinc foam, preferably zinc foil with a thickness of 100 μm.

[0025] The diaphragm is one of glass fiber, non-woven qualitative filter paper or polypropylene fiber diaphragm, preferably glass fiber.

[0026] The present invention also protects an aqueous zinc ion symmetrical battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte as described above.

[0027] Preferably, the positive electrode is any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy, and three-dimensional zinc foam, and the negative electrode is consistent with the positive electrode; more preferably, it is zinc foil with a thickness of 100 μm.

[0028] Preferably, the diaphragm is one of glass fiber, non-woven qualitative filter paper or polypropylene fiber diaphragm.

[0029] The present invention also protects an aqueous zinc ion asymmetric battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte as described above.

[0030] Preferably, the negative electrode is any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy, and three-dimensional zinc foam, preferably zinc foil with a thickness of 100 μm.

[0031] The positive electrode is any one of copper foil and titanium foil, preferably titanium foil with a thickness of 30 μm.

[0032] Preferably, the diaphragm is one of glass fiber, non-woven qualitative filter paper or polypropylene fiber diaphragm.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The complex electrolyte additive for the battery provided by the present invention is added as an aqueous zinc ion battery electrolyte additive, which can effectively alleviate the dendrite, corrosion, hydrogen evolution and passivation problems of the zinc negative electrode, thereby significantly improving the cycle stability and rate performance of the zinc negative electrode; the Cu in the Cu-EDTA complex additive 2+ It exists in the complex in the form of coordination. When it comes into contact with the zinc negative electrode in the electrolyte environment, it can spontaneously form a Cu metal electrode / electrolyte interface by substitution reaction. This interface can induce Zn 2+Directed deposition, thus achieving a dendrite-free zinc anode; during the dissolution process, the original Cu metal interface forms a protective CuZn5 alloy in situ, which significantly inhibits the side reactions of the interface; in addition, when Cu 2+ When dissociated from the Cu-EDTA complex, the EDTA anion will be released to interact with Zn in the solution. 2+ A coordination effect occurs, thereby optimizing the solubility structure of hydrated zinc ions, accelerating their deposition kinetics, reducing the activity of free water in the aqueous solution, and reducing uncontrollable side reactions and solid-liquid interface reactions on the surface of the zinc negative electrode, thereby effectively alleviating the corrosion, hydrogen evolution and passivation problems of the zinc negative electrode.

[0035] (2) The complex electrolyte additive for batteries provided by the present invention can form metal and alloy electrode-electrolyte interfaces on the surface of the zinc negative electrode through substitution and electrochemical reaction, respectively, and regulate the deposition behavior of zinc ions to inhibit the generation of zinc dendrites and accelerate the deposition / dissolution kinetics, thereby significantly extending the life of the zinc negative electrode and enhancing the rate performance; it can regulate the solvation structure of zinc ions, slow down side reactions such as hydrogen evolution, corrosion, and passivation, and when coupled with a high-efficiency positive electrode, it can significantly delay the capacity decay of aqueous zinc ion batteries; at the same time, the aqueous zinc ion battery electrolyte additive is low in price, green and environmentally friendly, and has strong functionality, which is conducive to the development of aqueous zinc ion battery electrolytes and aqueous zinc ion batteries with excellent performance, safety, environmental protection, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 (ae) are Zn / / Zn symmetric cells assembled using the electrolytes prepared in Examples 1-5 and Comparative Example 1, at 4 mA·cm -2 The current density is 4 mAh cm -2 Time-voltage diagram at deposition capacity; Figure 1 (f) is a Zn / / Zn symmetric battery assembled using the electrolytes prepared in Example 3 and Comparative Example 1. -2 Current density, 10 mAh cm -2 Time-voltage diagram for the deposition capacity.

[0037] Figure 2 At 10 mA cm -2 Current density, 10 mAh cm -2 In-situ optical microscope images of Example 3(a) and Comparative Example 1(b) at a deposition capacity of .

[0038] Figure 3 (a) Example 3 and Comparative Example 1 at 10 mA·cm -2 Current density, 10 mAh cm -2 XRD pattern of zinc foil at deposition capacity, Figure 3(b) is the comparison of relative crystal plane intensity.

[0039] Figure 4 For Example 3 (ab) and Comparative Example 1 (cd) at 10 mA·cm -2 Current density, 10 mAh cm -2 SEM image of zinc foil at deposition capacity.

[0040] Figure 5 The Zn / / Cu asymmetric battery assembled from Example 3 and Comparative Example 1 was tested at 8 mA·cm -2 The current density is 8 mAh cm -2 Coulombic efficiency diagram at deposition capacity.

[0041] Figure 6 The Zn / / δ-MnO2 fully symmetrical battery assembled from Example 6 and Comparative Example 2 was -1 Cycling performance diagram at current density of .

[0042] Figure 7 The in-situ symmetrical battery in Example 3 is 10 mA·cm -2 Current density, 10 mAh cm -2 Evolution of the deposition / stripping capacity during one cycle of Zn deposition-stripping was determined by XRD test.

[0043] Figure 8 for Figure 7 The corresponding relative crystal plane intensity in the XRD test.

[0044] Fig. 9 The in-situ symmetrical battery in Example 3 is 10 mA·cm -2 Current density, 10 mAh cm -2 XRD test of zinc deposition-stripping evolution process of deposition / stripping capacity after 1, 3, and 5 cycles. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Unless otherwise specified, the experimental methods involved in the embodiments of the present invention are all conventional methods; the materials, reagents, instruments, equipment, etc. used, unless otherwise specified, can be obtained through commercial channels.

[0047] Zinc foil preparation: The 100 μm thick zinc foil purchased from commercial channels was polished to remove the oxide layer and other impurities, cut into 12 mm diameter discs with a cutting machine, and then ultrasonically washed with ethanol and dried at low temperature for use as the positive / negative electrodes of the symmetrical half-cell of the battery, the negative electrode of the asymmetric half-cell, and the negative electrode of the full battery.

[0048] Diaphragm preparation: GF-D glass fiber diaphragm purchased from commercial channels was cut into 19 mm diameter discs using a cutting machine for later use.

[0049] Copper foil preparation: The copper foil purchased from commercial channels was cut into 16.2 mm diameter discs for use as the positive electrode of the asymmetric half-cell.

[0050] δ-MnO2 cathode preparation:

[0051] (1) First, prepare 5% PVDF (polyvinylidene fluoride) colloid: mix commercially purchased PVDF binder and NMP (N-methyl-pyrrolidone) solvent in a mass ratio of 1:19 and stir thoroughly to dissolve to obtain 5% PVDF colloid;

[0052] (2) δ-MnO2, acetylene black and PVDF binder (added in the form of 5% PVDF, the ratio is calculated according to PVDF binder) purchased from commercial channels are mixed in a mass ratio of 7:2:1, and then an appropriate amount of NMP is added to mix into a uniform slurry;

[0053] (3) The slurry was coated on a 30 μm thick titanium foil purchased from a commercial channel using a scraper, dried at 60 °C in a vacuum for 12 h, and then cut into 12 mm diameter positive electrode sheets using a cutting machine for later use. The active material loading was controlled at 0.9-1.4 mg cm -2 , which is used as the positive electrode of the full battery.

[0054] Example 1

[0055] A method for preparing an electrolyte comprises the following steps:

[0056] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 10 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) were weighed into deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4 and 0.2 g / L Cu-EDTA, which is the electrolyte.

[0057] The above electrolyte was used in a symmetrical battery, zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Example 1 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0058] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (a), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the conditions, the Zn / / Zn battery of Example 1 short-circuited at 271 h.

[0059] Example 2

[0060] A method for preparing an electrolyte comprises the following steps:

[0061] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 25 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) were weighed into deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4 and 0.5 g / L Cu-EDTA, which is the electrolyte.

[0062] The above electrolyte was used in a symmetrical battery, zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Example 2 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0063] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (b), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the conditions, the Zn / / Zn battery of Example 2 short-circuited at 373h.

[0064] Example 3

[0065] A method for preparing an electrolyte comprises the following steps:

[0066] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 50 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) were weighed into deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4 and 1.0 g / L Cu-EDTA, which is the electrolyte.

[0067] (1) The above electrolyte was used in a symmetrical battery. Zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Example 3 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0068] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (c), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the conditions of , Zn / / Zn battery shows low polarization voltage and cycle life exceeds 1250h; Figure 1 As shown in (f), at a current density of 10 mA cm -2 , deposition capacity is 10 mAh cm -2 Under the conditions, the polarization voltage is stable and the cycle life exceeds 680h.

[0069] (2) A 1 cm*1 cm zinc foil (100 μm thick) was used as the positive and negative electrodes, and the electrolyte prepared in Example 3 was assembled into a Zn / / Zn in-situ symmetrical battery.

[0070] The current density was 10 mA cm-1 under an in situ optical microscope. -2 , deposition capacity is 10 mAh cm -2 The zinc deposition effect was tested under the conditions of , and the test time was 1h. The zinc deposition effect of the Zn / / Zn in-situ symmetric battery of the electrolyte in Example 3 is as follows Figure 2 As shown in (a), no bubbles are generated during the whole process, and the zinc deposition is very smooth without dendrites.

[0071] The zinc sheets deposited in the Zn / / Zn in-situ symmetric cell of the electrolyte of Example 3 were tested by XRD (X-ray diffraction) instrument. Figure 3 As shown in the diffraction pattern of (a), after deposition, the position of the diffraction peaks of the zinc foil deposited in the electrolyte of Example 3 is basically consistent with the standard card PDF#04-0831 of bare zinc and Zn, but the intensity of all diffraction peaks is significantly reduced, which indicates that after the nucleation and growth of zinc ions in the electrolyte of Example 3, the grain radius of zinc is reduced, thereby obtaining a dense deposition layer.

[0072] In addition, if Figure 3 As shown in (b), the (101) crystal plane of zinc is used as a reference to compare the diffraction peaks of bare zinc. The relative intensity of the diffraction peaks is (101) / I (002) Increased from 1.25 to 6.09, I (101) / I (100) It increased from 2.88 to 2.89, which shows that the electrolyte of Example 3 can induce zinc ions to deposit on the Zn(101) crystal plane, which shows that Cu-EDTA has the function of regulating the uniform and directional deposition of zinc ions.

[0073] The surface morphology of the zinc sheet deposited in the Zn / / Zn in-situ symmetric cell of the electrolyte of Example 3 was observed by SEM (field emission scanning electron microscope). Figure 4As shown in (ab), after deposition, the surface is very flat and uniform, and the zinc ions are oriented to deposit at an angle of 65°, corresponding to the (101) crystal plane of zinc. This once again proves that Cu-EDTA can induce zinc ions to deposit oriented along the Zn (101) crystal plane and inhibit the growth of zinc dendrites.

[0074] (3) A zinc foil (100 μm thick) with a diameter of 12 mm was used as the negative electrode, a copper foil with a diameter of 16.2 mm was used as the positive electrode, and glass fiber was used as the separator. The electrolyte prepared in Example 3 was assembled into a CR2032 button-type Zn / / Cu asymmetric battery.

[0075] The assembled Zn / / Cu symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 5 As shown, at a current density of 8 mA cm -2 , deposition capacity is 8 mAh cm -2 Under the conditions of , the Zn / / Cu battery shows highly reversible deposition / stripping behavior, with an average Coulombic efficiency of 99.61% over 120 cycles.

[0076] Example 4

[0077] A method for preparing an electrolyte comprises the following steps:

[0078] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 75 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) were weighed into deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4 and 1.5 g / L Cu-EDTA, which is the electrolyte.

[0079] The above electrolyte was used in a symmetrical battery, zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Example 4 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0080] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (d), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the conditions, the Zn / / Zn battery of Example 4 short-circuited at 547h.

[0081] Example 5

[0082] A method for preparing an electrolyte comprises the following steps:

[0083] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 100 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) were weighed into deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4 and 2.0 g / L Cu-EDTA, which is the electrolyte.

[0084] The above electrolyte was used in a symmetrical battery, zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Example 5 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0085] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (e), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the conditions, the Zn / / Zn battery of Example 5 short-circuited at 279h.

[0086] Example 6

[0087] A method for preparing an electrolyte comprises the following steps:

[0088] Weigh 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte), 1.6901 g of manganese sulfate monohydrate (additive salt) and 50 mg of Cu-EDTA (complex electrolyte additive, the molar ratio of Cu to EDTA is 1:1) in deionized water to prepare 50 mL of a mixed solution containing 2 M ZnSO4, 0.2 M MnSO4 and 0.2 g / L Cu-EDTA, which is the electrolyte. The purpose of adding the additional salt is to maintain the stability of the MnO2 positive electrode.

[0089] The above electrolyte was used in a full battery, using a zinc foil (100 μm thick) with a diameter of 14 mm as the positive electrode, a δ-MnO2 positive electrode with a diameter of 12 mm as the positive electrode, and a GF / D glass fiber with a diameter of 19 mm as the separator. The electrolyte prepared in Example 6 was assembled into a CR2032 button-type Zn / / δ-MnO2 full battery.

[0090] The assembled Zn / / δ-MnO2 full battery was subjected to charge and discharge experiments on a blue-power test system. Figure 6 As shown, at a current density of 1A·g -1 Under the conditions of -1, after 380 cycles, the capacity retention rate can reach 113.6%, which shows that under the action of Cu-EDTA additive, the zinc negative electrode can maintain stability and ensure the supply of zinc source to the positive electrode.

[0091] Comparative Example 1

[0092] A method for preparing an electrolyte comprises the following steps:

[0093] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) was weighed into deionized water to prepare 50 mL of an aqueous solution containing 2 M ZnSO4, which is the electrolyte.

[0094] (1) The above electrolyte was used in a symmetrical battery, zinc foil (100 μm thick) with a diameter of 12 mm was used as the positive and negative electrodes, and glass fiber was used as the separator. The electrolyte prepared in Comparative Example 1 was assembled into a CR2032 button-type Zn / / Zn symmetrical battery.

[0095] The assembled Zn / / Zn symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 1 As shown in (c), at a current density of 4 mA cm -2 , deposition capacity is 4 mAh cm -2 Under the condition of , the Zn / / Zn battery of comparative example 1 short-circuited at 200h. Figure 1 As shown in (f), at a current density of 10 mA cm -2 , deposition capacity is 10 mAh cm -2 Under the conditions, the Zn / / Zn battery of Comparative Example 1 short-circuited at only 82 h.

[0096] (2) A 1 cm*1 cm zinc foil (100 μm thick) was used as the positive and negative electrodes, and the electrolyte prepared in Comparative Example 1 was assembled into a Zn / / Zn in-situ symmetrical battery.

[0097] The current density was 10 mA cm-1 under an in situ optical microscope. -2 , deposition capacity is 10 mAh cm -2 The zinc deposition effect was tested under the conditions of , and the test time was 1h. The zinc deposition effect of the Zn / / Zn in-situ symmetric battery of the electrolyte in comparative example 1 was as follows Figure 2 As shown in (b), the surface of the zinc foil gradually changed from smooth to rough during the whole process, which indicates that the zinc deposition was uneven when Cu-EDTA was not added.

[0098] The zinc sheets deposited in the Zn / / Zn in-situ symmetric cell of the electrolyte of Comparative Example 1 were tested by XRD (X-ray diffraction) instrument. Figure 3As shown in the diffraction pattern of (a), after deposition, the diffraction peak position of the zinc foil deposited in the electrolyte of Comparative Example 1 is basically consistent with the standard card PDF#04-0831 of bare zinc and Zn, but the intensity of the zinc (100) crystal plane is significantly enhanced. The direction of this crystal plane is perpendicular to the direction of the zinc plane, which will cause uncontrollable dendrite growth.

[0099] In addition, if Figure 3 As shown in (b), the (101) crystal plane of zinc is used as a reference to compare the diffraction peak of bare zinc. The relative intensity I of the diffraction peak of comparative example 1 is (101) / I (002) Increased from 1.25 to 1.5, I (101) / I (100) It decreases from 2.88 to 1.80, which indicates that the electrolyte of Comparative Example 1 cannot make zinc ions deposit uniformly and directional, and the direction of zinc deposition is irregular, which will aggravate the growth of dendrites.

[0100] The surface morphology of the zinc sheet deposited in the Zn / / Zn in-situ symmetric cell of the electrolyte of Comparative Example 1 was observed by SEM (scanning electron microscope). Figure 4 As shown in (cd), after deposition, a large number of irregular zinc dendrites appeared on the surface of the zinc sheet. Most of the zinc was deposited at a vertical angle of 90°, corresponding to the Zn (100) crystal plane, which is consistent with the XRD results.

[0101] (3) A zinc foil (100 μm thick) with a diameter of 12 mm was used as the negative electrode, a copper foil with a diameter of 16.2 mm was used as the positive electrode, and glass fiber was used as the separator. The electrolyte prepared in Comparative Example 1 was assembled into a CR2032 button-type Zn / / Cu asymmetric battery.

[0102] The assembled Zn / / Cu symmetrical battery was subjected to charge and discharge experiments on a blue-power test system. Figure 5 As shown, at a current density of 8 mA cm -2 , deposition capacity is 8 mAh cm -2 Under the conditions, the Zn / / Cu battery short-circuited after only 42 cycles, and the average coulombic efficiency was only 99.18%.

[0103] Comparative Example 2

[0104] A method for preparing an electrolyte comprises the following steps:

[0105] 28.755 g of zinc sulfate heptahydrate (zinc salt electrolyte) and 1.6901 g of manganese sulfate monohydrate (additional salt) were weighed into deionized water to prepare 50 mL of a mixed aqueous solution containing 2 M ZnSO4 and 0.2 M MnSO4, which is the electrolyte. The purpose of adding the additional salt is to maintain the stability of the MnO2 positive electrode.

[0106] The above-mentioned electrolyte was used in a full battery, using a zinc foil (100 μm thick) with a diameter of 14 mm as the positive electrode, a δ-MnO2 positive electrode with a diameter of 12 mm as the positive electrode, and a GF / D glass fiber with a diameter of 19 mm as the separator. The electrolyte prepared in Comparative Example 2 was assembled into a CR2032 button-type Zn / / δ-MnO2 full battery.

[0107] The assembled Zn / / δ-MnO2 full battery was subjected to charge and discharge experiments on a blue-power test system. Figure 6 As shown, at a current density of 1A·g -1 Under the conditions of , the initial specific capacity of the Zn / / δ-MnO2 full battery containing the electrolyte of Example 6 is 227.3 mAh·g -1 , after 100 cycles, the capacity retention rate can reach 87.7%.

[0108] The performance of the aqueous zinc ion batteries tested above is summarized in Table 1 below.

[0109] Table 1 Summary of performance of aqueous zinc ion batteries assembled from electrolyte samples of various embodiments and comparative examples

[0110]

[0111]

[0112] According to the results summarized in Table 1, the embodiments of the present invention use different concentrations of Cu-EDTA as an additive for the zinc ion battery electrolyte, and the cycle performance of the battery is significantly improved, especially when the concentration of Cu-EDTA is 1.0 g·L -1 When the battery cycle life reaches the maximum value, it indicates that 1.0g·L -1 It is the optimal addition concentration of Cu-EDTA additive.

[0113] In order to further study the mechanism of action of Cu-EDTA additive in Zn-ion batteries during cycling, XRD tests were performed on the Zn deposition-stripping evolution process at a current density of 10 mA cm -2 , deposition / stripping capacity is 10mA·cm -2 Under the conditions of , the zinc foil in Example 3 is deposited in 0-60min and peeled off in 60-120min. Figure 7 (a) with Figure 8 As shown, during the deposition process, the relative intensity of the diffraction peak I (002) / I (100) is gradually decreasing, and I (101) / I (002)This indicates that the Cu-EDTA additive can induce the directional deposition of zinc ions in the direction of the Zn(101) crystal plane, thereby obtaining a uniform dense layer and inhibiting the growth of dendrites. Figure 7 (b) with Figure 8 As shown, during the peeling process, the relative intensity of the diffraction peak I (002) / I (100) Gradually increasing, and I (101) / I (002) It gradually decreases, which indicates that the deposition of zinc is highly reversible. In addition, it is special that CuZn5 alloy is gradually produced during the stripping process, which will protect the stability of the zinc negative electrode during the cycle and extend the life of the aqueous zinc-ion battery.

[0114] Finally, if Fig. 9 As shown in the XRD diagram, the CuZn5 alloy layer can still remain stable after multiple cycles, which indicates that the CuZn5 alloy is highly stable and can achieve long-term protection of the zinc negative electrode.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A complex electrolyte additive for a battery, characterized in that: The electrolyte additive is a complex containing metal ions; the complex consists of a central ion and an internal ligand.

2. The battery complex electrolyte additive according to claim 1, characterized in that: The central ion is Cu 2+ , Cu + , Fe 3+ , Fe 2+ 、Co 2+ , Sb 2+ 、Cd 2+ , Gd 3+ , Ga 3+ Sn 2+ The internal ligand is one or more of acetylacetone, pyrophosphate, ethylenediaminetetraacetic acid, hydroxyethylethylenediaminetriacetic acid, tartaric acid, citric acid, nitrilotriacetic acid and their salts; the molar ratio of the central ion to the internal ligand is between 1:10 and 10:

1.

3. An electrolyte for an aqueous zinc ion battery, characterized in that: The electrolyte contains the complex electrolyte additive for battery according to any one of claim 2, and the addition amount of the electrolyte additive is 0.001-20 g / L.

4. The electrolyte according to claim 3, characterized in that The electrolyte also includes a zinc salt electrolyte and an aqueous solvent, wherein the zinc salt electrolyte is one or more of zinc sulfate, zinc chloride, zinc perchlorate, zinc bromide, zinc acetate, zinc nitrate, zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonyl imide and hydrates thereof, and the concentration of the zinc salt electrolyte is 1-3 mol / L.

5. The electrolyte according to claim 3, characterized in that The electrolyte also includes an additional salt, wherein the additional salt contains Mn 2+ The salt is one or more of manganese sulfate, manganese chloride, manganese perchlorate, manganese bromide, manganese acetate, manganese nitrate, manganese trifluoromethanesulfonate, manganese bis(trifluoromethanesulfonyl imide) and hydrates thereof, and the concentration of the additional salt is 0.01-4 mol / L.

6. The electrolyte according to claim 3, characterized in that The electrolyte can also be used in aqueous zinc ion supercapacitors and aqueous zinc-iron liquid flow batteries.

7. An aqueous zinc ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte as claimed in any one of claims 3 to 6.

8. The aqueous zinc ion battery according to claim 7, characterized in that: The positive electrode includes a positive electrode active material and a positive electrode current collector, wherein the positive electrode active material is at least one of a manganese-based material, a vanadium-based material, a Prussian blue analogue, polyaniline, elemental iodine, and basic zinc sulfate, and the positive electrode current collector is at least one of titanium foil, titanium mesh, stainless steel foil, stainless steel mesh, carbon paper, carbon cloth, and nickel foam; the negative electrode is a zinc metal material, including any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy, and three-dimensional zinc foam; the diaphragm is one of glass fiber, non-woven qualitative filter paper, or polypropylene fiber diaphragm.

9. An aqueous zinc ion symmetrical battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the electrolyte according to claim 3 or 4, wherein the positive electrode is any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy and three-dimensional zinc foam, the negative electrode is consistent with the positive electrode, and the separator is one of glass fiber, non-woven qualitative filter paper or polypropylene fiber separator.

10. An aqueous zinc ion asymmetric battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the electrolyte according to claim 3 or 4, wherein the negative electrode is any one of zinc sheet, zinc plate, zinc foil, zinc powder, zinc alloy and three-dimensional zinc foam, the positive electrode is any one of copper foil and titanium foil, and the separator is one of glass fiber, non-woven qualitative filter paper or polypropylene fiber separator.

Citation Information

Patent Citations

  • Zinc ion battery electrolyte containing additive, preparation method of zinc ion battery electrolyte and zinc ion battery

    CN113948779A

Cited By

  • Aqueous zinc ion battery electrolyte and aqueous zinc ion battery

    CN120280574A

  • Aqueous zinc ion battery electrolyte containing maleamic acid, battery and preparation method

    CN120341402A

  • Electrolyte system for in-situ repair of zinc negative electrode alloy interface and preparation method thereof

    CN120709533A

  • Electrolyte and zinc-based battery

    CN120933505A

  • Electrolyte, preparation method thereof and aqueous zinc ion battery

    CN121812780A